"We have lovers to the sea and to the land": representations of sport in feuillentons (Rio de Janeiro; 1851-1855) - Melo, Victor Andrade de (Brazilian journal of physical education and sport, 2013)
Considering the relevance of the material published in the first Brazilian feuilletons, the aim of this study is to discuss the presence of the sport in Rio de Janeiro early years of the second half of the nineteenth century (1851-1855) from the representations of three pioneers of chronic Brazilian: José Maria Paranhos, Francisco Otaviano and José de Alencar. We were stimulated by some not casual coincidences: the initial moments of a practice, represented in the first moments of a literary genre, in a period when there was some political and economic stability, in which some groups began to aspire to adopt modern ideas.